Essential Oil from the Leaves of Chromolaena odorata, and Sesquiterpene Caryophyllene Oxide Induce Sedative Activity in Mice - Godfried Dougnon; Michiho Ito (MDPI AG, 2021)
Chromolaena odorata (L.) R.M.King & H.Rob. essential oil (COEO) was investigated for its sedative activity in mice. The results showed that COEO significantly reduced mice locomotor activity and the most efficient concentrations were 0.04 and 0.00004 mg/cage (volume of the cage 61.2L). Analysis of chemical composition of the oil indicated that caryophyllene oxide (43.75%) was the major compound and bioactivity-guided fractionation of the oil was performed to isolate the compound responsible for activity. The data clearly identified sesquiterpene caryophyllene oxide as the compound inducing COEO sedative activity and it was effective in decreasing mice locomotor activity by 56% and 57% at 0.0004 and 0.04 mg/cage, respectively. In order to understand the action mechanisms, caryophyllene oxide was tested for its effects on the central nervous system (CNS) by using a caffeine pre-excited mice test and a pentobarbital sleeping-induced test in mice. The results showed that caryophyllene oxide is a potent CNS depressant. Nevertheless, it fails to potentiate the effects of pentobarbital on the GABAergic system, nor did flumazenil, a GABAA receptor antagonist, reversed its effects. It was especially interesting to note that β-caryophyllene, the precursor of caryophyllene oxide, demonstrated a similar pattern of sedative activity, and the present work further extends actual knowledge on these naturally occurring sesquiterpenes. The findings in this study reveal the new activity of caryophyllene oxide as an innovative way to manage sleep and CNS-related disorders, and demonstrates a satisfactory effect of two interesting sesquiterpene compounds on the CNS.